"I Love Tater Tot Casserole, I Just Make It Vegan": Applying the Communication Theory of Identity to Examine Vegans' Identity Management Techniques. Issue 4 (4th July 2021) - Paxman, Christina G.
ABSTRACT: This qualitative analysis reflects 40 interviews that were conducted with vegans residing throughout the United States. The communication theory of identity was used as a guiding framework to examine the identity management techniques vegans employ within the personal, enacted, relational, and communal frames of identity. Thematic analysis yielded one communal theme of veganism ( Negative Stereotypes of Veganism ) that influences the ways vegans manage their identity at the enacted level. Two themes emerged ( Facilitating Smooth Interactions, Eating and Sharing Vegan Food ) to explain how vegans refute negative stereotypes and enact a positive identity. To facilitate smooth interactions, participants reported withholding their identity, downplaying their identity, and not imposing their views on others. Results indicate that vegans also use food as a form of identity management. Participants explained that they eat vegan food, share vegan food with others, and plan ahead (e.g., by reviewing restaurant menus online) to manage their identity. Results of this study demonstrate that vegans enact their identity in ways that are thoughtful and strategic.